Evolution of weak discontinuity waves in non-ideal interstellar environments - Shweta; Chaturvedi R.K.; Srivastava S.K.; Singh L.P. (My University, 2025)
A systematic method is used to study the problem of propagation of planar, cylindrically symmetric and spherically symmetric shock waves of the one-dimensional motion of an inviscid, self-gravitating, non-ideal interstellar gas cloud. The analytic solution of the problem is resolved, which specifies non-linear behavior in the physical plane. The transport equation, which describes the evolution of weak discontinuity in non-ideal gas is derived. It is observed that the nature of the solution completely depends on the net volumetric cooling rate and self-gravitating parameter. It is observed that an increase in the value of self-gravitating parameter results in delay of process of shock formation and shock forms early when heating dominates cooling in the system. Also, expansive waves take less time to decay in planar geometry as compared to cylindrical and spherical geometries and compressive waves take more time to develop shocks for cylindrical and spherical geometries as compared to planar geometry. © 2023, Indian Academy of Sciences.